Building a Management Information System for Juvenile Welfare Centre in the UAE and Investigate the Effectiveness of its Implementation - ZAZA, SARWEEN (2017)
This project investigates the use of a management information software system for juvenile welfare centre in UAE by assessing the staff’s performance in operating the project and examining the viability of the software system implementation in applying the work- streams. A review of the juvenile share system was carried out to understand how different government handles the juvenile offensive cases and the need for further actions. In any case, is was noted from research made that juvenile beneath age 18, that are found to commit serious offences are taken to correction facilities to be evaluated, and certain measures are taken by the government to ensure such children are reoriented. The research demonstrated the software system by collecting and analysing data after building the software interface. The interview was carried out with the staff of Al Mafraq Juvenile Welfare Centre to crevice the efficiency of the software. The outcome of the exercise was limited to the computer literacy or operability of the staff’s.